Radiotherapy-induced xerostomia: a randomised, double-blind, controlled trial of Visco-ease™ oral spray compared with placebo in patients with cancer of the head and neck. Issue 10 (December 2019) - Paterson, C.; Thomson, M.C.; Caldwell, B.; Young, R.; McLean, A.; Porteous, S.; Clark, S.; Messow, C.M.; Kean, S.; Grose, D.; Lamb, C.; Rizwannullah, M.; et al.
Abstract: Radiotherapy-induced xerostomia (RIX) is a common and untreatable side effect of radiotherapy to the head and neck. Visco-ease™ mouth spray (Lamellar Biomedical Ltd), a new product that is made from lamellar body mimetics, reduces the viscosity of saliva ex vivo. The purpose of this study was to evaluate its safety and effectiveness in the treatment of RIX in 43 patients with cancer of the head and neck. They were randomised into the Visco-ease™ or placebo groups, and asked to complete the Groningen radiotherapy-induced xerostomia (GRIX) questionnaire each week. The primary endpoint was a change in GRIX score from baseline to end of treatment. There was no difference in scores between the two groups, and none of the patients had device-related serious adverse events. Visco-ease™ oral spray was safe and tolerable but no better than placebo in reducing RIX in this group of patients.